2013
DOI: 10.1186/1471-2369-14-99
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes associated with acute kidney injury following ruptured abdominal aortic aneurysm

Abstract: BackgroundCurrent data describing the epidemiology of acute kidney injury (AKI) following repair of ruptured abdominal aortic aneurysm (rAAA) are limited and long-term outcomes are largely unknown. Our objectives were to describe the incidence rate, risk factors, clinical course and long-term outcomes of AKI following rAAA repair.MethodsRetrospective population-based cohort study of all referrals undergoing emergency repair of rAAA in Northern Alberta from January 1, 2002 to December 31 2009. Demographic, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…Since mortality increases with increasing AKI severity, exclusion of non-survivors mainly affects the recovery pattern of more severe forms of AKI. Worsening renal recovery with increasing severity of AKI confirms previous findings [4,11,15,19,20] and underscores the importance of clearly reporting AKI severity, including the need for RRT in stage 3.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Since mortality increases with increasing AKI severity, exclusion of non-survivors mainly affects the recovery pattern of more severe forms of AKI. Worsening renal recovery with increasing severity of AKI confirms previous findings [4,11,15,19,20] and underscores the importance of clearly reporting AKI severity, including the need for RRT in stage 3.…”
Section: Discussionsupporting
confidence: 72%
“…The available reports used definitions based on absence of RIFLE criteria [4,17,24], return to baseline serum creatinine (Screat) [11,19,27], or a discharge Screat that returned to a value below 1.1 or 1.25 times baseline [7,10,16,20]. Few studies reported recovery according to AKI severity [4,11,15] and none of these studies used the KDIGO criteria [28] for both diagnosis of AKI and for assessment of recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative renal dysfunction is the most common complication of aneurysm repair requiring SC aortic clamping [14] [16] [17], and is associated with not only increased in-hospital morbidity and mortality but also adverse long-term outcomes [18] [19]. The effects of renal ischemic time and clamping level on postoperative renal function have been primarily examined in non-ruptured pararenal AAAs.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] With the emergence of consensus criteria to standardize the definition of this postoperative complication, especially with mild and moderate degrees of AKI, recent studies within the vascular literature have demonstrated that AKI prevalence ranges from 13%-76% and is associated with adverse perioperative outcomes. [11][12][13][14] Many of these studies have focused on the prevalence of AKI after a specific procedure using small patient cohorts.…”
Section: Introductionmentioning
confidence: 99%